Hubungan Depresi Terhadap Perilaku Makan Mahasiswa Tingkat Akhir Fakultas Kesehatan Masyarakat (FKM), Universitas Teuku Umar - Nurhidaya, Nurhidaya; Muliadi, Teuku; Putri, Enda Silvia; Anwar, Sufyan (Medan Resource Center, 2024)
Unhealthy eating behaviors represent a significant issue among university students, particularly those experiencing academic and psychological pressures. These conditions can lead to stress and anxiety, which may escalate into depression. Furthermore, the adverse effects of unhealthy eating behaviors driven by depression can severely impact students' health, often resulting in neglect of nutritional intake. This negligence contributes to nutritional problems such as malnutrition, overnutrition, and the onset of chronic diseases. This study aims to examine the relationship between depression and eating behaviors among final-year students at the Faculty of Public Health, Universitas Teuku Umar. Utilizing a quantitative cross-sectional approach, the study involved a population of 223 final-year students, with a sample size of 70 selected in 2023/2024. Conducted in June 2024, the research employed questionnaires for primary data collection. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. Results revealed a significant association between depression and eating behaviors (p = 0.001, CI 95% = 1.899–15.902). Among the participants, 64.3% exhibited depressive symptoms, and 61.4% demonstrated unhealthy eating behaviors. The analysis indicated that students with depression were 1.94 times more likely to engage in unhealthy eating behaviors. This study concludes that depression significantly increases the risk of unhealthy eating behaviors among final-year students.